Louis Pasteur, the Father of Immunology? - Smith, Kendall A. (Frontiers in Immunology, 2012)
Louis Pasteur is traditionally considered as the progenitor of modern immunology because of his studies in the late 19th century that popularized the germ theory of disease, and that introduced the hope that all infectious diseases could be prevented by prophylactic vaccination, as well as also treated by therapeutic vaccination, if applied soon enough after infection. However, Pasteur was working at the dawn of the appreciation of the microbial world, at a time when the notion of such a thing as an immune system did not exist, certainly not as we know it today, more than 130 years later. Accordingly, why was Pasteur such a genius as to discern how the immune system functions to protect us against invasion by the microbial world when no one had even made the distinction between fungi, bacteria or viruses, and no one had formulated any theories of immunity. A careful reading of Pasteur’s presentations to the Academy of Sciences reveals that Pasteur was entirely mistaken as to how immunity occurs, in that he reasoned, as a good microbiologist would, that appropriately attenuated microbes would deplete the host of vital trace nutrients absolutely required for their viability and growth, and not an active response on the part of the host. Even so, he focused attention on immunity, preparing the ground for others who followed. This review chronicles Pasteur’s remarkable metamorphosis from organic chemist to microbiologist to immunologist, and from basic science to medicine.